Pemanfaatan Model Pembelajaran Futuristik Berbasis Artificial Intelligence (AI) dalam Dunia Pendidikan - Hasanah, Amalia; Budiyono, Slamet (Al-DYAS, 2024)
The use of Artificial Intelligence (AI) in the world of education is considered relevant in the context of futuristic learning in this modern era. This article describes the use of futuristic learning models based on Artificial Intelligence (AI) and its positive and negative impact. The purpose of writing this article is to provide a comprehensive understanding of Artificial Intelligence (AI) and its use in the world of education. The data used in this article is information from various literary sources, among them are scientific articles, research results, books and news related to the use of Artificial Intelligence (AI) in the world of education. Based on the results of the data collected by the author, use of AI in education has great potential to improve efficiency and effectiveness in education so that in the end can improve the quality of education especially in Indonesia. However, the use of AI still needs to bear in mind the potential negative impacts such as the risk of dependence, the ethical challenges and the important role of human interaction.